2023
DOI: 10.1111/joor.13408
|View full text |Cite
|
Sign up to set email alerts
|

Randomised controlled trial on testing an increased vertical dimension of occlusion prior to restorative treatment of tooth wear

Abstract: Background: Evaluation of a new vertical dimension of occlusion (VDO) in complex restorative treatments is considered a necessary step prior to placement of restorations.Objectives: This randomised controlled trial (RCT) aimed to assess the effects of using an evaluation of a VDO increase before restorative treatment in patients with moderate-to-severe tooth wear, on OHRQoL, freeway space (FWS) and interventions to restorations.Methods: Forty-two patients with tooth wear were included and randomly allocated to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Constricted mandibular range of motion can compromise freeway space, limiting the resting position and impacting occlusal stability and patient comfort. In cases of inadequate bimaxillary clearance, unstable unilateral chewing dynamics may result 33 . Explainability analyses indicated that AI performed better when considering phonetic expression, clenching muscle activity, and TMJ vibrations during lateral and anterior protrusion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Constricted mandibular range of motion can compromise freeway space, limiting the resting position and impacting occlusal stability and patient comfort. In cases of inadequate bimaxillary clearance, unstable unilateral chewing dynamics may result 33 . Explainability analyses indicated that AI performed better when considering phonetic expression, clenching muscle activity, and TMJ vibrations during lateral and anterior protrusion.…”
Section: Discussionmentioning
confidence: 99%
“…Persistent clenching and bruxism, leading to occlusal changes, tooth wear, and muscle tension, have an important influence on the vertical dimension at rest 33 . Some of these parafunctional habits are more prevalent in younger patients and often necessitate orthodontic intervention 35 .…”
Section: Discussionmentioning
confidence: 99%